2017
DOI: 10.1108/prog-02-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

From owning to sharing: understanding the emergence of social sharing services

Abstract: Purpose The purpose of this paper is to identify the motivational factors that help shape user perceptions of and attitudes toward car-sharing services and develop a research model that integrates these factors with the technology acceptance model to explicate car sharing’s adoption pattern. Design/methodology/approach An online survey was administered to examine the role of proposed motivational factors for the adoption of wearable healthcare devices. Confirmatory factor analysis and structural equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
10
1
Order By: Relevance
“…The findings of this paper do not concur with those reported byWang et al (2019) orHwang and Griffiths (2017). Specifically, Amirkiaee and Evangelopoulos (2018) showed that in case of high anxiety with transportation, the trust in ridesharing stakeholders, together with economic and time benefits, will encourage people to join ridesharing Kim et al (2017). identified motivational variables that frame riders' perceptions of and attitudes toward ridesharing services and proposed a research model including motivational factors and those from the technology acceptance model to explain the adoption of car sharing.…”
contrasting
confidence: 79%
“…The findings of this paper do not concur with those reported byWang et al (2019) orHwang and Griffiths (2017). Specifically, Amirkiaee and Evangelopoulos (2018) showed that in case of high anxiety with transportation, the trust in ridesharing stakeholders, together with economic and time benefits, will encourage people to join ridesharing Kim et al (2017). identified motivational variables that frame riders' perceptions of and attitudes toward ridesharing services and proposed a research model including motivational factors and those from the technology acceptance model to explain the adoption of car sharing.…”
contrasting
confidence: 79%
“…Along with environmental benefits, carpoolers can benefit from shared travel costs, time savings from driving in high occupancy vehicle (HOV) lanes, decreased commuting stress, and, in certain situations, preferential parking and other incentives [9,13,14]. Additionally, carpooling services enable two or more unrelated individuals to share a trip or a portion of a trip, with passengers contributing to the driver's expenses [15,16]. Some non-profit carpooling programs are community-based initiatives (cooperatives) that broaden the scope of shared mobility beyond commercial models.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for them, using shared ride-hailing services has become as easy as using any other digital platform for shopping, bill payment and searching for information (Ahuja & Khazanchi, 2016). Hence, it is not surprising that although this factor is important, its effects is decreasing as people have becoming familiar with the technology (Kim et al, 2017;Sheppard & Vibert, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These benefits led to the perception of the usability of the sharing mobility amongst commuters. Furthermore, a direct and positive relationship has been found between the PU and users' behavioural intentions (Haldar & Goel, 2019;Kim, Choi, Kim, & Park, 2017;Roy, 2017) to use the sharing mobility space. Since shared ride-hailing is one form of sharing mobility, it is assumed that commuters' intention will be positively affected by its perceived usefulness.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 93%